The latest trends in internet of things usage in smart homes: a systematic literature review - Widianto, Mochammad Haldi; Prabowo, Puji (International Journal of Advances in Applied Sciences, 2025)
The Internet of Things (IoT) has recently developed very quickly. Equipped with increasingly mature information technology, especially for use in smart homes. This technology is integrated with IoT systems, which can now solve this problem. This paper helps discover the latest research trends and offers a broad perspective on what factors are used in intelligent housing by utilizing a systematic literature review (SLR). This article takes 2256 documents from Springer, IEEE, ACM, MDPI, ScienceDirect, Hindawi, IAES, and Google Scholar. 59 articles passed the specified exclusion and inclusion criteria. Furthermore, the new findings are that several research factors exist in smart homes, such as Artificial Intelligence (AI), Assistant Technology, Blockchain, IoT, energy-saving IoT, Network IoT, Robot IoT, and Security IoT. It is hoped that future research will provide insights to examine smart homes based on their factor.